THE IMPLEMENTATION OF AIR (AUDITORY, INTELLECTUALLY, AND REPETITION) LEARNING MODEL BASES FLASHCARD MEDIA TO IMPROVE PROBLEM SOLVING SKILL OF PLANE GEOMETRY - Eka Agustina Khairunnisa; Riyadi Riyadi; Hasan Mahfud (Universitas Sebelas Maret, 2018)
The purpose of this research is to improve problem solving skill of plane geometry by applying Auditory Intellectually and Repetition (AIR) learning model bases Flashcard in the fifth grade students of State Elementary School Mangkubumen Kulon No.83 in academic year 2017/2018. This form of research is a Classroom Action Research and it was conducted three cycles. Each cycle consists of four steps there are planning, action, observation, and reflection. Data collection techniques are using tests, observations, interviews and documentation. Data validity tests are using content validity and triangulation. Data analysis technique used is the interactive model. The result of the assessment of study activity and teacher performance appraisal also increase. Based on the result of the research, it can be concluded that through the application of Auditory Intellectually and Repetition (AIR) learning model bases Flashcard can improve improve problem solving skill of plane geometry for V grade students of SD N Surakarta in the academic year 2017/2018.